PENGEMBANGAN LKPD BERBASIS INKUIRI TERBIMBING MATERI STRUKTUR DAN FUNGSI JARINGAN PADA TUMBUHAN DI SMAN 8 PONTIANAK - Herra Wastu Widanti; Laili Fitri Yeni; Titin Titin (Bioilmi: Jurnal Pendidikan, 2023)
One of activities that can involve students’ activeness in learning according to the demand of 2013 curriculum is inquiry learning. The practical and operational teaching materials that can support student learning activities are LKPD. This study aims to find out the feasibility and students' response to guided inquiry-based LKPD in Structure and Function of tissue plant for students in grade XI of SMAN 8 Pontianak. The method used in this research is Research and Development (RnD) with a development model by Borg and Gall that was conducted through several steps, there are potential and problems, data collection, product design, design validation, design revision, and product trial. Instruments used in this research are product validation sheet and students' response sheet. There were 5 validators. The result of V Aiken's analysis for aspects of content feasibility, linguistics, presentation, and graphics get an average score of 0,90, therefore it is indicated as valid. The result of students' responses gets an average score from the aspect of cognition, affection, and conation of 90,44% which is very positive. From the result that has been obtained, it can be concluded that the developed LKPD is feasible to be used as teaching materials.